Sires' MC1R Genotypes and Coat Color of the Offspring of the Chikso (Korean Brindle Cattle) - Jae-Hee Park; Chang-Woo Lee; Hae-Lee Lee; Jae Won Choi; Yun Ho Choy; A-Nam Kwon; Yeoen Hee Ji; Jong Gug Kim (The Korean Society of Animal Reproduction and Biotechnology, 2014)
The objective of this study was to determine the effect of the MC1R genotypes of the Chikso (Korean brindle cattle) sires on the coat colors of their offspring. In this study, 15 Chikso sires with known MC1R genotypes were used for breeding in the Gangwon Province Livestock Research Center, the Chungbuk Institute of Livestock and Veterinary Research, and the Livestock Experiment Station, Jeonbuk Institute of Livestock and Veterinary Research from either 2011 or 2012 to 2013. There were 6 sires with E+E+ genotypes and 9 sires with E+e genotypes, and their coat colors were all whole brindle (more than 50 of the body). Among the 90 calves produced in 2011~2013 or 2012~2013 from the 15 sires, 50 (55.6%) of them were females and 40 (44.4%) of them were males. Coat colors of the offspring were determined when they reached over 6 months of age. Calves with whole brindle, part brindle, brown and black coat colors were 42 (48.3%), 11 (12.6%), 18 (20.7%) and 16 (18.4%), respectively. Ratio of calves with whole brindle coat color was higher than any other coat colors. Among the offspring with whole brindle color, 20 (41.7%) calves were female and 22 (51.3%) calves were male. By determining the MC1R genotypes of the dams and calves in this study along the family lines, and investigating other genes that may be involved in the coat colors of the Chikso, better breeding system may be established to increase the brindle coat color appearance in the future.